Politik Dinasti dan Pembaruan Sistem Demokrasi di Indonesia - Firdaus Arifin (Fakultas Hukum Universitas Islam Indonesia, 2024)
Political dynasty has grown into one of the main challenges in the development of democracy in Indonesia since the 1998 Reformation Era which aims to strengthen democracy and governance based on Good Governance. Thus, the existence of cultured political dynasty has the potential to hinder the achievement of democratic objectives and legal reforms developed in Indonesia. This study aims to identify and analyze the impact of political dynasty on the development of the democratic system with a focus on the reform of Constitutional Law. The method used in this study is a juridical-normative approach, with a qualitative analysis of related laws and regulations and a study of the practice of political dynasty in Indonesia. The results of the study indicate that the existing legal framework remains inadequate to limit political dynasties, which exploit loopholes in regulations and weak supervision to maintain power. In addition, the practice of political dynasty undermines the principles of meritocracy and accountability that should be the basis for democratic governance. Therefore, a more comprehensive renewal of the democratic system is needed, including the implementation of a cooling-off period for incumbent family members, strengthening supervision of the election process, increasing public political education, and limiting the influence of money in politics. The implications of this study emphasize the importance of improving regulation and supervision to strengthen democracy and reduce the dominance of political dynasty, which will ultimately strengthen democratic governance and decentralization.Keywords: Democracy, Decentralization, Legal Reform, Political Dynasties. AbstrakPolitik dinasti telah menjadi salah satu tantangan utama dalam perkembangan demokrasi di Indonesia sejak Era Reformasi tahun 1998 yang bertujuan untuk memperkuat demokrasi dan pemerintahan yang berlandaskan Good Governance. Dengan demikian, keberadaan politik dinasti yang membudaya, berpotensi menghambat pencapaian tujuan demokrasi dan pembaruan hukum yang dikembangkan di Indonesia. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis dampak politik dinasti terhadap perkembangan sistem demokrasi dengan fokus pada pembaruan Hukum Tata Negara. Metode yang digunakan dalam penelitian ini adalah pendekatan yuridis-normatif, dengan analisis kualitatif terhadap peraturan perundang-undangan terkait serta studi terhadap praktik politik dinasti di Indonesia. Hasil penelitian menunjukkan bahwa kerangka hukum yang ada masih belum memadai untuk membatasi dinasti politik, yang memanfaatkan celah dalam regulasi serta lemahnya pengawasan untuk mempertahankan kekuasaan. Selain itu, praktik politik dinasti merusak prinsip meritokrasi dan akuntabilitas yang seharusnya menjadi landasan bagi pemerintahan yang demokratis. Oleh karena itu, pembaruan sistem demokrasi yang lebih komprehensif diperlukan, termasuk penerapan masa jeda (cooling-off period) bagi anggota keluarga petahana, penguatan pengawasan terhadap proses pemilihan, peningkatan pendidikan politik masyarakat, serta pembatasan pengaruh uang dalam politik. Implikasi dari penelitian ini menekankan pentingnya perbaikan regulasi dan pengawasan untuk memperkuat demokrasi dan mengurangi dominasi politik dinasti, yang pada akhirnya akan memperkuat tata pemerintahan yang demokratis dan desentralisasi.Kata Kunci: Demokrasi, Desentralisasi, Pembaruan Hukum, Politik Dinasti.